Histéresis y asimetría en delitos: un análisis de los robos a nivel colonia en la Zona Metropolitana de Guadalajara - Cortez Yactayo, Willy Walter (El Colegio de México A.C., 2017)
One of the characteristics of crime that has been underestimated in empirical studies is its persistence over time and, consequently, its asymmetric response to changes in its explanatory variables. The importance of the hysteresis effect has been noted in several studies, which argue that it can significantly reduce the effectiveness of anti-crime policies. Using reports of various types of robberies at the neighborhood level in the Metropolitan Area of Guadalajara (ZMG), we find that these crimes have a strong hysteresis component, and display asymmetric behavior in response to changes in economic conditions.